1998
DOI: 10.1002/(sici)1098-2795(199806)50:2<128::aid-mrd2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo study of pluripotency in intraspecific hybrid cells obtained by fusion of murine embryonic stem cells with splenocytes

Abstract: Hypoxanthine phosphoribosyltransferase–deficient (HPRT‐) mouse embryonic stem (ES) cells, HM‐1 cells (genotype XY), were fused with adult female DD/c mouse spleen cells. As a result, a set of HAT‐resistant clones was isolated. Four hybrid clones most similar in morphology and growth characteristics to the HM‐1 cells were studied in detail with respect to their pluripotency. Of these, three clones contained 41–43 chromosomes, and one clone was nearly tetraploid. All the clones had the XXY set of sex chromosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 41 publications
4
74
0
2
Order By: Relevance
“…Most hybrid cells had antigen ECMA-7, a marker typical of early mouse embryos (Pascoe et al 1992), and showed high activity of alkaline phosphatase. A series of experiments in which "injected" chimeras were produced with significant contribution of hybrid cells validated the pluripotency capacities of hybrid cells (Matveeva et al 1998). In fact, analysis of biochemical markers (glucose phosphate isomerase) and coat color demonstrated the presence of the descendants of donor hybrid cells in most chimeric tissues.…”
Section: Pluripotency Of Embryonic Hybrid Cells and Reprogramming Of mentioning
confidence: 88%
See 4 more Smart Citations
“…Most hybrid cells had antigen ECMA-7, a marker typical of early mouse embryos (Pascoe et al 1992), and showed high activity of alkaline phosphatase. A series of experiments in which "injected" chimeras were produced with significant contribution of hybrid cells validated the pluripotency capacities of hybrid cells (Matveeva et al 1998). In fact, analysis of biochemical markers (glucose phosphate isomerase) and coat color demonstrated the presence of the descendants of donor hybrid cells in most chimeric tissues.…”
Section: Pluripotency Of Embryonic Hybrid Cells and Reprogramming Of mentioning
confidence: 88%
“…Various in vitro and in vivo tests were used to assess the pluripotency of the hybrid cells. All the clones examined, when kept in suspension, maintained the developmental potential to form embryoid bodies containing the derivatives of all three embryonic germ layers (Matveeva et al 1998). Most hybrid cells had antigen ECMA-7, a marker typical of early mouse embryos (Pascoe et al 1992), and showed high activity of alkaline phosphatase.…”
Section: Pluripotency Of Embryonic Hybrid Cells and Reprogramming Of mentioning
confidence: 99%
See 3 more Smart Citations